Building an online platform for African farmer organisations - Ben Rejeb, Fatma; Addison, Chris (Technical Centre for Agricultural and Rural Cooperation, 2016)
The Pan-African Farmers' Organization was created in 2010 to organise farmers and defend their interests by promoting valuable knowledge management tools